Design and implementation of an electronic control system based on fpga, which to climate conditions of a greenhouse for tomato culture in the city of tacna, 2018 - Molanes Miovich, Cándido (2019)
The purpose of the thesis was to design and implement a control system that will optimize the climatic conditions of a greenhouse. The system was based on an FPGA development platform, specifically the Nexys 4 ddr of digilent; the main focus of the thesis was the reconfigurability and flexibility of the hardware in the future. To this end the control system used was a 32-bit microprocessor microblaze which collected data measured by sensors and based on a control algorithm developed, it maintained automatically the parameters determined by the expert in agronomy. The parameters to control were: temperature, relative humidity and humidity of the soil, desirable in a tomato greenhouse in the city of Tacna. The temperature and relative humidity were maintained in a range of (24 - 26) ° C and (70 and 80) % respectively, and it was achieved that the humidity of the soil reaches half of the root of the plant. To measure the temperature and relative humidity, the SHT85 sensor was selected with a measuring range (-40 to 105) ° C and (0 to 100) % respectively. The soil moisture measurement was made using the VH400 sensor with dimensions of (9.3x3.9x0.7) cm that has a millimeter strip. In addition, it showed the variables measured in a display console on the monitor of a laptop taking advantage of the data sent and received by the UART port of the FPGA card.